Advocacy, partnership and political commitment for TB vaccine research. (August 2016) - Olesen, Ole F.; Chan, Sharon; Chappell, Janice; Guo, Yan; Leite, Luciana C.C.
Summary: The 4th Global Forum on TB Vaccines, convened in Shanghai, China, from 21 – 24 April 2015, brought together a wide and diverse community involved in tuberculosis vaccine research and development to discuss the current status of, and future directions for this critical effort. This paper summarizes the sessions on Advancing the Pipeline: A Vision for the Next Decade, Engaging the BRICS: Basic Research to Manufacturing, and Regulatory and Access Issues for New TB Vaccines. Summaries of all sessions from the 4th Global Forum are compiled in a special supplement of Tuberculosis .[August 2016, Vol 99, Supp S1, S1–S30] .